The Effectiveness of Group Counseling with Self-Disclosure and Modeling Techniques to Increase the Cultural Awareness of Counselor Candidates - Mungin Eddy Wibowo; Anita Sukma Fatimahtul zahro’; Dwi Yuwono Puji Sugiharto (Jurnal Bimbingan Konseling, 2024)
Counselor candidates with high cultural awareness will be able to make new friends, develop good interpersonal skills, face stereotypes and prejudices about other cultures, create harmony between groups, and be more adaptive in a multicultural world. Regarding this issue, the present research strived for increasing cultural awareness in counselor candidates by implementing group counseling through a humanistic approach, a self-disclosure technique and a behavioral approach named modeling technique. It was a quantitative experimental study in the form of a two-factor pretest-multiple posttest control design. 30 research subjects were divided equally in the control group, the experimental group with a self-disclosure technique and the experimental group with a modeling technique. The subject data were collected using a culture awareness scale and analyzed using the repeated-measures mixed ANOVA test. It was found that the implementation of group counseling with the self-disclosure and modeling techniques was effective in increasing the cultural awareness of Guidance and Counseling students at UIN Salatiga. It is recommended that counselors use the same treatment to increase their cultural awareness.